BVR Standardization of the CCD Photometric System of Chungbuk National University Observatory - Jang-Hae Jeong; Yong-Sam Lee; Chun-Hwey Kim; Yo-Na Yoon (Journal of Astronomy and Space Sciences, 2009)
BVR observations for 52 standard stars were performed using the 1-m reflecter with 2K CCD System of Chungbuk National University Observatory(CBNUO) in 2008. We obtained 1,322 CCD images to establish a correlation between our bvr system and the standard Johnson-Cousins BVR system. We derived the tentative equations of transformation between then as follows; V = v-0.0303(B-V)+0.0466